Impact of biofertilizer application and phosphorus levels on the growth and yield of soybean (Glycine max L.) - KAUR, RAMANDEEP; KAUR, MANDEEP; SAINI, SAT PAL (Journal of Soil and Water Conservation, 2024)
The present investigation was carried out at experimental area of agriculture research farm, Guru Kashi University, Talwandi Sabo, Bathinda, Punjab during Kharif 2019 to ascertain the effect of application of rhizobium seed inoculation along with phosphorous on various growth parameters and yield of soybean. The results showed that application of rhizobium seed inoculation and phosphorus resulted in significantly highest growth parameters viz. plant height, leaf area index, no. of branches/plant and dry matter accumulation and yield attributes like no. of pod/plant, number of seeds per pod, pod length and test weight as well as seed and stover yield than the control. Inoculation of rhizobium recorded 8.04% higher seed yield than control. Application of phosphorus at the rate of 100 kg ha-1 recorded 23.13% higher seed yield than control.